Activated CD8(+) T cell extracellular vesicles prevent tumour progression by targeting of lesional mesenchymal cells - Seo, Naohiro (Nat Commun, 2018)
Fibroblastic tumour stroma comprising mesenchymal stem cells (MSCs) and cancer-associated fibroblasts (CAFs) promotes the invasive and metastatic properties of tumour cells. Here we show that activated CD8(+) T cell-derived extracellular vesicles (EVs) interrupt fibroblastic stroma-mediated tumour progression. Activated CD8(+) T cells from healthy mice transiently release cytotoxic EVs causing marked attenuation of tumour invasion and metastasis by apoptotic depletion of mesenchymal tumour stromal cells. Infiltration of EV-producing CD8(+) T cells is observed in neovascular areas with high mesenchymal cell density, and tumour MSC depletion is associated with preferential engulfment of CD8(+) T cell EVs in this setting. Thus, CD8(+) T cells have the capacity to protect tumour progression by EV-mediated depletion of mesenchymal tumour stromal cells in addition to their conventional direct cytotoxicity against tumour cells.